Produksi dan Isolasi Protein Membran Stadium Bradizoit Toxoplasma gondii : Suatu Usaha untuk Mendapatkan Material Diagnostik dalam Mendiagnosa Toksoplasmo - Hanafiah, Muhammad; Nurcahyo, Wisnu; Kamaruddin, Mufti; Karmil, Fadrial (Jurnal Veteriner; Vol 10 No 3 (2009))
A study was conducted to isolate the membrane protein of Toxoplasma gondii at bradyzoid stage for the development of intradermal diagnostic test in livestock infected by the parasite. Toxoplasma was initially collected from meat of goat serologically positive to the parasite. The infected meat was then fed into uninfected cat to obtain oocyst. The oocyst was inoculated into the stomach of mice to produce tachyzoit which in turn produce cyst in tissue known as bradyzoit . The membrane protein was then isolated from the bradyzoit. The protein was analysed by sodium dodecyl sulfate electrophoresis (SDS-PAGE). The data obtained were presented descriptively. The protein concentration isolated from each mouse infected at the dose of 1x107 oocysts was 11.91 mg. Two protein bands specific for bradyzoit were identified at 97.72 kDa and 67.60 kDa.
Keywords: Isolation, protein, bradyzoit, T. gondii